THE ROLE AND POSITION OF SOCIAL SCIENCES ON CHARACTER EDUCATION IN THE INDEPENDENT CURRICULUM - Marsini (RADJA PUBLIKA, 2023)
Social Sciences (IPS) is an instructive program that has materials Training from different disciplines of Social Sciences and Mankind (Schooling and history) coordinated and introduced logically and mentally with the end goal of instruction in view of Pancasila and Indonesian Culture. IPS too can be said to be a fusion or fusion of various subjects social so in friendly examinations subjects use parts certain from the social sciences. On a fundamental level, social examinations training in primary schools doesn't show the Social Sciences as disciplines, yet rather conceptualizes the quintessence of the Social Sciences to shape understudies into residents productive member of society. Accordingly as a work in character building, So there should be congruity with the way of life of this country. The implementation is not solely carried out in schools through a progression of learning exercises instructing, yet can be held a progression of self-improvement exercises that did beyond school.Habituations in life, For example, strict, genuine, trained, open minded, diligent, harmony adoring, dependable, participation, fair and mindful,it needs to start from the smallest scope such as family up to a wider scope in society. Values This certainly needs to be developed which in the end can shaping the personal character of students which further constitutes a reflection of the life of a nation.